Utilization Of Non-Wood Forest Products (Ntfps) By The Community Around The Protected Forest Area Kalotok Village, North Luwu Regency - Wiwi Pradini; Srida Mitra Ayu; Witno Witno (Jurnal Penelitian Kehutanan BONITA, 2022)
This study aims to determine the use of NTFPs by the community around the Kalotok protected forest area and to determine the use of NTFPs by the community around the protected forest area. This research was conducted in Kalotok Village, Sabbang District, North Luwu Regency. This research was conducted from April to June 2021. The method used was an interview method using a questionnaire. The number of respondents as many as 60 people. Data analysis used descriptive qualitative method. The results of the study obtained data as many as 9 types of Non-Timber Forest Products (NTFPs) which are used by communities around protected forest areas. The NTFPs used by the community are Durian, langsat, rattan, honey, bamboo, melinjo and sugar palm.